O intuitivo e o lógico no conhecimento matemático: análise de uma proposta pedagógica em relação a abordagens filosóficas atuais e ao contexto educacional da matemática - Geromel Meneghetti, Renata Cristina [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2009)
In this paper, we consider Meneghetti & Bicudo's proposal (2003) regarding the constitution of mathematical knowledge and analyze it with respect to the following two focuses: in relation to conceptions of mathematical knowledge following the fundamentalist crisis in mathematics; and in the educational context of mathematics. The investigation of the first focus is done analyzing new claims in mathematical philosophy. The investigation of the second focus is done firstly via a theoretical reflection followed by an examination of the implementation of the proposal in the process of development of didactic materials for teaching and learning Mathematics. Finally, we present the main results of the application of one of those materials.
The Intuitive and the Logical in Mathematical Knowledge: analysis of a pedagogical proposal from a viewpoint of new philosophical approaches and in the educational context of mathematics
Keywords: Mathematical Knowledge; Intuitive Aspect; Logical Aspect; Philosophy of Mathematics; Mathematics Education; Pedagogical Proposal